Access to electronic resources by visually impaired people - Jenny Craven (Information Research: An International Electronic Journal)
Research into access to electronic resources by visually impaired people undertaken by the Centre for Research in Library and Information Management has not only explored the accessibility of websites and levels of awareness in providing websites that adhere to design for all principles, but has sought to enhance understanding of information seeking behaviour of blind and visually impaired people when using digital resources.